METODE PENANAMAN KARAKTER DI MASA NEW NORMAL PADA ANAK USIA 3-4 TAHUN KB TUNAS HARAPAN - Lina Eka Retnaningsih; Nadya Nela Rosa; Mhd. Abror (incrementapedia, 2022)
This study aims to investigate the methods of instilling character values in the new normal period in children aged 3-4 years in Tunas Harapan playgroup. The change from the pandemic period to the new normal has changed the learning activities that were previously learned from home into face-to-face learning while still paying attention to health protocols. This study uses a qualitative descriptive method. The data collection techniques were observation and documentation of the learning activities, as well as interviews with children, teachers, and parents. Data were analyzed using data reduction, data display, and conclusion/verification. The results showed that the methods of instilling character values in the new normal period used in Tunas Harapan playgroup were very diverse. The methods were playing traditional games, exemplification and habituation, storytelling, singing, and field trip. With the return of children playing while learning at school, the application of these methods has become very effective especially after more than two years of online learning. Children became more enthusiastic in following the learning activities at school and good character values were embedded in the children.